A longitudinal analysis of within-education-group earnings inequality - Magnus Gustavsson (Uppsala University, Department of Economics, 2008)
Using a large Swedish longitudinal database for the period 1982-2005, I estimate and compare within-group inequality in persistent and transitory earnings among men with high-school and college degrees. Analyses of inequality over the life cycle reveal that experience-variance profiles of persistent earnings are very similar across the two education groups and also consistent with standard human capital models of on-the-job training. Transitory earnings shocks display a marked U-shaped variance pattern over the life-cycle for both groups, but are clearly larger for high-school graduates and also account for a larger proportion of their overall variance. Analyses of changes in within-group inequality over time, holding life-cycle effects constant, show that high-school and college graduates have been subject to similar trend growths in both persistent and transitory earnings differentials between 1982 and 2005.
urn:nbn:se:uu:diva-86784
Keywords: C33; D31; J39; 330; Permanent inequality; Earnings instability; Life-cycle earnings; Schooling; Einkommensverteilung; Akademiker; Lebenszyklus; Schweden